Chromatin remodeling (SWI/SNF) complexes, cancer, and response to immunotherapy. Issue 9 (2nd September 2022) - Krishnamurthy, Nithya; Kato, Shumei; Lippman, Scott; Kurzrock, Razelle
Abstract : Chromatin regulation involves four subfamilies composed of ATP-dependent multifunctional protein complexes that remodel the way DNA is packaged. The SWItch/Sucrose Non-Fermentable (SWI/SNF) chromatin remodeling complex subfamily mediates nucleosome reorganization and hence activation/repression of critical genes. The SWI/SNF complex is composed of the BRG-/BRM-associated factor and Polybromo-associated BAF complexes, which in turn have multiple subunits. Significantly, ~20% of malignancies harbor alterations in >1 of these subunits, making the genes encoding SWI/SNF family members among the most vulnerable to genomic aberrations in cancer. ARID1A is the largest subunit of the SWI/SNF complex and is altered in ~40%–50% of ovarian clear cell cancers and ~15%–30% of cholangiocarcinomas, in addition to a variety of other malignancies. Importantly, outcome was improved after immune checkpoint blockade (ICB) in patients with ARID1A -altered versuss wild-type tumors, and this result was independent of microsatellite instability or tumor mutational burden. Another subunit—PBRM1—is mutated in ~40% of clear cell renal cell carcinomas and ~12% of cholangiocarcinomas; there are contradictory reports regarding ICB responsiveness. Two other SWI/SNF subunits of interest are SMARCA4 and SMARCB1. SMARCA4 loss is the hallmark of small cell carcinoma of the ovary hypercalcemic type (and is found in a variety of other malignancies); SMARCA4 germline alterations lead to rhabdoid tumor predisposition syndrome-2; SMARCB1 germline alterations, rhabdoid tumor predisposition syndrome-1. Remarkable, although anecdotal, responses to ICB have been reported in both SMARCA4 -aberrant and SMARCB1 -aberrant advanced cancers. This review focuses on the role that SWI/SNF chromatin remodeling subunits play in carcinogenesis, the immune microenvironment, and in immunotherapy responsiveness.